P–733 In infertile patients, risk factors for environmental reprotoxic exposure are widespread, limited in number and modifiable. (6th August 2021) - Prades, S; Sunyach, C; Courbiere, B; Metzler-Guillemain, C; Bretelle, F; Sari-Minodier, I; Perrin, J
Abstract: Study question: What are the risk factors for environmental reprotoxic exposure in infertile patients? Summary answer: The most represented categories of reprotoxic risk factors (RRF) were dietary exposures (86% of patients), overweight (46%), psychoactive substances (38%) and male occupational exposures (63%). What is known already: Numerous studies have reported the deleterious effects of environmental reprotoxic exposures on male or female fertility. These studies most often focus on the impact of a limited number of reprotoxic risk factors (body mass index (BMI), dietary habits, tobacco or alcohol consumption) or a limited number of chemical or physical reprotoxic exposures: phthalates, occupational exposures, or pesticides. Despite the call of several reproductive health professional societies and public health agencies for taking environmental health into account in women of childbearing age, this approach remains little realized in current practice. Study design, size, duration: We conducted a prospective, monocentric study between June 2018 and February 2020 in women and men visiting the fertility unit of our University Hospital for assisted reproduction technique (ART) treatment. Participants/materials, setting, methods: Patients completed a self-questionnaire to collect information about i) the various types of exposure to RRF, and ii) frequency and intensity of exposures (qualitative and semi-quantitative approach). We performed a literature search in order to define the environmental factors and the exposure level thresholds associated with a "recognized" or "suspected" RRF and we analyzed their nature and number in patients. Main results and the role of chance: During the inclusion period, we received 545 couples in consultation, and 405 were included in this study (810 patients/1090, participation rate: 74%). 65% of women and 68% of men self-reported at least one "recognized" RRF. In men, they were from exposure to solvents, heat, psychoactive substances and a BMI>25; in women, from exposure to poor indoor air quality, psychoactive substances and a BMI>25. A limited number of recognized risk factors were recorded in the majority of patients (one, two or three risk factors in 65% of patients). Men were more often exposed than women to occupational risk factors (63% of men versus 28% of women) such as solvents and ambient heat, and women were more often exposed than men to poor indoor air quality and volatile organic compounds (49% of women versus 30% of men). We note that the majority of the risk factors for reprotoxic exposure found were modifiable, specifically dietary, occupational, overweight and psychoactive substance exposures. Limitations, reasons for caution: One limitation is the collection of data via a self-administered questionnaire, which makes it possible to estimate the risk factors for reprotoxic exposure, but not to detect them in a measurable way, for example, through exposure biomarkers. In addition, no data is available about all RRF in the general population. Wider implications of the findings: We suggest that if the individual screening of each infertile patient's RRF was done before ART, most patients could act on a limited number of modifiable RRF, in the aim of increasing their chances of natural pregnancy and improving ART outcomes. Trial registration number: N° 2018–13–06–004 (Ethics Committee of the University of Aix Marseille) and N° 2020–27 (Assistance Publique - Hôpitaux de Marseille General Regulation on Data Protection).